Lombok Tourism Information System with Gamification-Based Quest and Reward Features - Patrialis Akbar; Ida Ayu Dewi Purnama Anjani; Indira Felista Sanis Suparsa; Tri Shandy Ananta Axell Saputra; Muhammad Daffa Dzaki Ahnaf; Herliana Rosika; Cynthia Corrêa (Tinta Emas Publisher, 2025)
The development of digital-based tourism applications in Lombok is one solution to improve the tourist experience and support local business actors. This study used a quantitative survey method involving 40 tourist respondents and qualitative interviews with traders and tourism managers in strategic locations such as Goa Lawah Village and Narmada Park. Data analysis showed that the majority of tourists have a high interest in interactive features such as gamification, points/reward systems, interactive maps, and cultural and historical content in tourism applications. In addition, respondents also showed a strong interest in local applications made in the region as a source of tourism information. The interview results support the survey findings by stating that the development of gamification-based applications can increase tourist visits and local merchant income. These findings form the basis for the development of an innovative and sustainable tourism platform in Lombok, which can increase the attractiveness of the destination while strengthening the local economy.